Sosialisasi dan Edukasi Remaja tentang Manfaat Tablet Tambah Darah untuk Meningkatkan Kepatuhan Konsumsi di Puskesmas Buntu Pane - Hanas, Yuni; Juni, Malisa; Christiani, Meity (Jurnal Masyarakat Indonesia (Jumas), 2025)
This counseling aims to determine the relationship between adolescents' knowledge level and their compliance with iron supplementation tablets at SMAN 1 Buntu Pane in 2025. Anemia, especially in adolescent girls, is a significant health problem, and iron supplementation tablets are one way to prevent it. However, compliance with iron supplementation tablets is often low, which may be influenced by adolescents' level of knowledge about the importance of iron supplementation. This counseling consisted of 35 randomly selected students. Data were collected through a questionnaire that measured their level of knowledge and compliance with iron supplementation tablets. Data analysis was carried out using the Pearson correlation statistical technique to determine the extent of the relationship between the two variables. The results of this counseling are expected to provide insight into the importance of increasing adolescents' knowledge about the benefits of iron supplementation tablets, as well as strategies to increase their compliance in taking them. This counseling is expected to contribute to designing more effective health programs in schools to address the problem of anemia in adolescents.